Method for producing inorganic metal oxide powder containing coated particles

By using rotary flow layer coating technology on inorganic metal oxide powder, the specific surface area increase is controlled to be less than 5.0, and the resin fluidity and operability problems caused by excessive specific surface area of ​​the coated powder in the prior art are solved, thereby realizing the following: Good filling and dispersibility.

CN119421859APending Publication Date: 2025-02-11DENKA CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380049457.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-28
Filing Date
2023-06-19
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

In the prior art, the specific surface area of ​​the coated inorganic metal oxide powder is prone to be too large, resulting in a decrease in fillingability and dispersion in the resin, loss of fluidity, and deterioration of operability.

Method used

The rotary flow layer coating technology is used to spray the raw material inorganic metal oxide powder with a slurry containing the coating component and sintered, so that the increase in BET specific surface area after coating is controlled to be less than 5.0.

Benefits of technology

The increase in the specific surface area of ​​the powder after coating is effectively suppressed, good fluidity and operability in the resin are maintained, and problems of lowering fillability and dispersion are avoided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005205845050000171
    Figure BDA0005205845050000171
Patent Text Reader

Abstract

Provided is a method for producing an inorganic metal oxide powder containing coated particles, in which the BET specific surface area of the finally obtained inorganic metal oxide powder has a small increase in the BET specific surface area relative to the BET specific surface area of a starting material powder, and the BET specific surface area of the starting material powder is less than the BET specific surface area of the starting material powder. And the flowability is not easily reduced when the resin is filled. A method for producing an inorganic metal oxide powder (I) containing coated particles (X), the method comprising spraying a slurry (C) containing a coating component (B) onto an inorganic metal oxide powder (A) as a starting material, applying a rotating flow layer, and then firing, and obtaining an inorganic metal oxide powder (I) containing the coated particles (X), wherein the ratio (Si) / (Sa)) of the BET specific surface area (Si) of the inorganic metal oxide powder (I) to the BET specific surface area (Sa) of the inorganic metal oxide powder (A) is 5.0 or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for producing an inorganic metal oxide powder containing coated particles. Background Art

[0002] In the field of semiconductor sealing materials, inorganic metal oxide powders such as silica and alumina are used as fillers for the purpose of improving thermal expansion coefficient, thermal conductivity, flame retardancy, etc. The thermal conductivity of silica is low. In addition, although alumina has a higher thermal conductivity than silica, it also has a high hardness, so the equipment used is prone to wear. Therefore, magnesium oxide powder, which has a higher thermal conductivity than silica and alumina and a lower hardness than alumina, is being studied as a filler that can be applied to the above fields.

[0003] It is known that magnesium oxide has low moisture resistance and reacts with moisture in the atmosphere to form magnesium hydroxide. If the content of magnesium hydroxide increases, the thermal conductivity tends to decrease, so the surface of magnesium oxide particles is coated to improve moisture resistance (for example, Patent Documents 1 and 2).

[0004] Prior art

[0005] Patent Document 1: Japanese Patent Application Publication No. 2003-34523

[0006] Patent Document 2: Japanese Patent Application Publication No. 2008-74683 Summary of the invention

[0007] However, in the conventional method for producing coated inorganic metal oxide powder, the specific surface area of ​​the powder increases due to coating. This is due to the fact that the shape and surface smoothness of the particles constituting the powder change due to coating, but if the BET specific surface area increases more significantly than before coating, it becomes difficult to obtain the desired physical properties. In addition, the filler of the inorganic metal oxide powder is generally mostly filled in the resin for use, so if the specific surface area becomes too large, there is a problem that the filling and dispersibility of the resin are reduced, the fluidity is lost, and the handling is deteriorated.

[0008] Therefore, the object of the present invention is to provide a method for producing an inorganic metal oxide powder containing coated particles, which is a method for producing an inorganic metal oxide powder containing particles whose surfaces are coated (coated particles), wherein the increase in the BET specific surface area of ​​the inorganic metal oxide powder finally obtained relative to the BET specific surface area of ​​the raw material powder is small, and the fluidity is not easily reduced when filled in a resin.

[0009] As a result of intensive studies, the present inventors have found that all of the above-mentioned technical problems can be solved by using a production method including a step of coating a raw material inorganic metal oxide powder by tumbling fluidized bed coating, thereby completing the present invention.

[0010] That is, the present invention has the following aspects.

[0011] [1] A method for producing an inorganic metal oxide powder (I), which is a method for producing an inorganic metal oxide powder (I) containing coated particles (X), wherein the above-mentioned production method includes the steps of spraying a slurry (C) containing a coating component (B) onto a raw material inorganic metal oxide powder (A), performing a rotating fluidized bed coating, and then sintering to obtain an inorganic metal oxide powder (I) containing coated particles (X), and the ratio of the BET specific surface area (Si) of the inorganic metal oxide powder (I) to the BET specific surface area (Sa) of the inorganic metal oxide powder (A) ((Si) / (Sa)) is 5.0 or less.

[0012] [2] The method for producing an inorganic metal oxide powder (I) according to [1], wherein the calcination temperature is 500 to 1600°C.

[0013] [3] The method for producing an inorganic metal oxide powder (I) according to [1] or [2], wherein the calcination time is 0.1 to 12 hours.

[0014] [4] A method for producing an inorganic metal oxide powder (I) as described in any one of [1] to [3], wherein the inorganic metal oxide powder (A) is sprayed with a slurry (C), wherein the proportion of the coating component (B) is in the range of 1 to 25 mass % relative to the total amount (100 mass %) of the inorganic metal oxide powder (A) and the coating component (B).

[0015] [5] A method for producing an inorganic metal oxide powder (I) as described in any one of [1] to [4], wherein the median particle size (Da50) of the inorganic metal oxide powder (A) is 10 to 150 μm, and the median particle size (Di50) of the inorganic metal oxide powder (I) is 11 to 300 μm.

[0016] [6] The method for producing an inorganic metal oxide powder (I) as described in any one of [1] to [5], wherein the above (Si) / (Sa) is 0.5 or more.

[0017] [7] The method for producing an inorganic metal oxide powder (I) according to any one of [1] to [6], wherein the coating component (B) contains an inorganic metal oxide powder (B1).

[0018] [8] The method for producing an inorganic metal oxide powder (I) according to any one of [1] to [7], wherein the coated particles (X) contain core-shell particles.

[0019] [9] A method for producing an inorganic metal oxide powder (I) as described in any one of [1] to [8], wherein the inorganic metal oxide powder (A) contains an inorganic metal oxide powder or an inorganic metal composite oxide powder containing at least one element selected from titanium, aluminum, magnesium, silicon and calcium.

[0020]

[10] A method for producing an inorganic metal oxide powder (I) as described in any one of [1] to [9], wherein the inorganic metal oxide powder (A) contains magnesium oxide powder, the coating component (B) contains at least one inorganic metal oxide powder (B1) selected from aluminum oxide powder and silicon dioxide powder, and the coated particles (X) contain particles whose surfaces are coated with a coating layer and which are core particles containing magnesium oxide.

[0021]

[11] The manufacturing method as described in

[10] , wherein the above-mentioned coating layer contains at least one selected from Al2O3, MgO-Al2O3 composite oxide, SiO2, and MgO-SiO2 composite oxide.

[0022] According to the present invention, a method for producing an inorganic metal oxide powder containing coated particles can be provided, wherein the BET specific surface area of ​​the finally obtained inorganic metal oxide powder has a small increase relative to the BET specific surface area of ​​the raw material powder and the fluidity is not easily reduced when filled in a resin. DETAILED DESCRIPTION

[0023] An embodiment of the present invention is described in detail below. The present invention is not limited to the following embodiments, and can be implemented by adding appropriate changes within the scope that does not hinder the effects of the present invention. When a specific description recorded in one embodiment is also applicable to other embodiments, the description is sometimes omitted in other embodiments. In this specification, the expression "α~β" indicating a numerical range means "above α and below β". In addition, in this specification, "powder" means "an aggregate of particles".

[0024] [Method for producing inorganic metal oxide powder (I) containing coated particles (X)]

[0025] The present embodiment relates to a method for producing an inorganic metal oxide powder (I), which is a method for producing an inorganic metal oxide powder (I) containing coated particles (X), wherein the above-mentioned production method includes the steps of spraying a slurry (C) containing a coating component (B) onto a raw material inorganic metal oxide powder (A), performing a rotating fluidized layer coating, and then sintering to obtain an inorganic metal oxide powder (I) containing coated particles (X), wherein the ratio of the BET specific surface area (Si) of the inorganic metal oxide powder (I) to the BET specific surface area (Sa) of the inorganic metal oxide powder (A) ((Si) / (Sa)) is 5.0 or less. According to the production method of the present embodiment, an inorganic metal oxide powder (I) can be produced, wherein the increase in the BET specific surface area of ​​the inorganic metal oxide powder finally obtained relative to the BET specific surface area of ​​the raw material powder is small, and the fluidity is not easily reduced when filled in a resin.

[0026] The inorganic metal oxide powder (I) (hereinafter sometimes referred to as "powder (I)") containing coated particles (X) obtained by the production method of the present embodiment has a BET specific surface area of ​​the inorganic metal oxide powder (I) that is finally obtained that is small in increase relative to the BET specific surface area of ​​the inorganic metal oxide powder (A) of the raw material. In the present embodiment, the increase in specific surface area before and after coating is represented by the ratio ((Si) / (Sa)) of the BET specific surface area (Si) of the inorganic metal oxide powder (I) to the BET specific surface area (Sa) of the inorganic metal oxide powder (A) of the raw material. According to the production method of the present embodiment, (Si) / (Sa) can be suppressed to 5.0 or less. The closer (Si) / (Sa) is to 1.0, the smaller the change in the BET specific surface area between the inorganic metal oxide powder (A) of the raw material (hereinafter sometimes referred to as "raw material powder (A)") and the powder (I).

[0027] The increase in BET specific surface area due to coating is caused by changes in the shape of the particles constituting the powder, a decrease in the surface smoothness of the particles (i.e., an increase in surface roughness), etc. The production method of this embodiment can easily suppress the decrease in the surface smoothness of the particles due to coating, and thus the value of (Si) / (Sa) can be 5.0 or less.

[0028] In one embodiment, the lower limit of (Si) / (Sa) may be 0.5 or more. That is, (Si) / (Sa) may be in the range of 0.5 to 5.0. When (Si) / (Sa) is less than 1.0, the BET specific surface area (Si) of the powder (I) is smaller than the BET specific surface area (Sa) of the raw material powder (A).

[0029] As a method for producing coated powder, it is known to coat the raw powder by immersing the raw powder in an aqueous solution containing a coating component and then calcining it. With such a method, it is very difficult to suppress the increase in the BET specific surface area of ​​the coated powder to be small, and further, it is very difficult to make the specific surface area of ​​the coated powder smaller than the specific surface area of ​​the raw powder. The reason is that in the above-mentioned method, although the filter cake layer obtained by filtering the raw powder and the coating component mixed in the solution is crushed and then calcined to obtain the coated powder, it is very difficult to uniformly and smoothly coat the coated component on the surface of the raw powder after crushing. The manufacturing method of this embodiment can uniformly and densely coat each particle constituting the raw powder (A) by using a rotating fluidized bed coating, and the crushing step of the previous method is no longer necessary, so the increase in the specific surface area of ​​the powder (I) can be suppressed. Therefore, the manufacturing method of this embodiment can also adjust (Si) / (Sa) to less than 1.0. In a preferred embodiment, (Si) / (Sa) may be 0.5 to 4.0, 0.5 to 3.0, or 0.5 to 2.0. (Sa) and (Si) may be measured under the following conditions.

[0030] (BET specific surface area measurement method)

[0031] The specific surface area is measured by filling 5 g of the raw material powder (A) (or powder (I)) in the measuring tank of a fully automatic specific surface area measuring device (BET one-point method) (for example: Macsorb HMmodel-1201 fully automatic specific surface area measuring device manufactured by Mountech). The degassing conditions before the measurement are set to 200° C. and 10 minutes. In addition, helium and nitrogen (mixed concentration: 30.5%) are used as the carrier gas and the adsorption gas, respectively.

[0032] <Raw material inorganic metal oxide powder (A)>

[0033] In the manufacturing method of the present embodiment, the raw material powder (A) can be any powder of an inorganic metal oxide without any particular limitation. In addition, "inorganic metal oxide" refers to a compound formed by a metal element and oxygen bond. In the present embodiment, as the raw material powder (A), an inorganic metal oxide powder preferably used in the field of semiconductor sealing materials can be used, but it is not limited thereto. As inorganic metal oxide powders preferably used in the field of sealing materials, for example, inorganic metal oxide powders or inorganic metal composite oxide powders containing at least one element selected from titanium, aluminum, magnesium, silicon and calcium can be cited. "Inorganic metal composite oxide" refers to a high-order oxide composed of an oxide containing two or more metal ions. As the raw material powder (A), it is preferred to contain the above-mentioned inorganic metal oxide powder or inorganic metal composite oxide powder. Among them, from the viewpoint of obtaining a powder (I) with good thermal conductivity, the raw material powder (A) preferably contains an inorganic metal oxide powder or inorganic metal composite oxide powder containing at least one element selected from aluminum and magnesium, and more preferably a powder containing magnesium oxide. In one embodiment, the raw material powder (A) may also be composed only of magnesium oxide powder.

[0034] (Magnesium oxide powder)

[0035] When the raw material powder (A) contains magnesium oxide powder, the purity of the magnesium oxide powder is not particularly limited, and is preferably determined according to the purpose. For example, when the powder (I) obtained by the manufacturing method of this embodiment is used as a filler for a semiconductor sealing material, it is preferred to use magnesium oxide powder with a purity of 90% or more, and more preferably to use magnesium oxide powder with a purity of 95% or more. In addition, magnesium oxide powder can be manufactured by a conventionally known method, for example, it can be manufactured by a method such as an electric melting method, a sintering method, etc.

[0036] In one embodiment, the diameter of the periclase crystallite of the magnesium oxide powder is preferably 50×10 -9 m or more. If the crystallite diameter is 50×10 -9 m or more magnesium oxide powder, the thermal conductivity tends to become good. In addition, "crystal diameter" refers to the value calculated by Scherrer formula using X-ray diffraction. When the particles are polycrystalline, the crystallite diameter represents the average value of the size of the single crystal in the polycrystalline.

[0037] (Physical properties of raw material powder (A))

[0038] In one embodiment, from the viewpoint of fluidity, the BET specific surface area (Sa) of the raw material powder (A) may be 0.01 to 20 m 2 / g, or 0.01~10m 2 / g, or 0.01~1m 2 / g.

[0039] In one embodiment, from the viewpoint of fluidity, the median particle size (Da50) of the raw material powder (A) may be 10 to 150 μm, 20 to 140 μm, 40 to 130 μm, or 45 to 120 μm. As long as the median particle size (Da50) of the raw material powder (A) is within the above range, the change in specific surface area is likely to be reduced when coating is performed using a rotating fluidized layer coating. In addition, in this specification, "median particle size (D50)" refers to the particle size measured using a laser diffraction particle size distribution measuring device (for example: Beckman Coulter (Co., Ltd.), product name "LS13 320"; MicrotracBEL (Co., Ltd.), product name "MT3300EXII", etc.), and the cumulative value is equivalent to 50% in the volume-based cumulative particle size distribution. The cumulative particle size distribution is represented by a distribution curve with the horizontal axis being the particle size (μm) and the vertical axis being the cumulative value (%).

[0040] The average circularity (ARa) of the raw material powder (A) is not particularly limited. In one embodiment, from the perspective of the filling property of the resin, the average circularity (ARa) may be 0.70 or more, 0.80 or more, or 0.90 or more. In addition, the average circularity may be measured by the following method.

[0041] (Method for measuring average circularity)

[0042] After fixing the raw material powder (A) (or powder (I)) with a carbon tape, osmium coating is performed. Thereafter, the particles are photographed at a magnification of 200 to 50,000 times using a scanning electron microscope (e.g., manufactured by JEOL Ltd., product name "JSM-7001F SHL"), and the projected area (A) of the particles is calculated using an image analyzer (e.g., manufactured by Nippon Roper Ltd., product name "Image-Pro Premier Ver.9.3"). p ) and the projected circumference (L), the circularity is calculated by the following formula (1). The circularity is calculated for any 200 particles and the average value is taken as the average circularity.

[0043] Roundness = 4πA p / L 2 ···(1)

[0044] The manufacturing method containing the previous wet coating is easily affected by the surface state of the raw material particles. When a raw material powder containing particles with low surface smoothness (large surface roughness) is used, the proportion of the uncoated part increases, and thus the specific surface area of ​​the obtained powder is easily increased. According to the manufacturing method of this embodiment, even when a powder containing particles with low surface smoothness is used as the raw material powder (A), it is easy to obtain coated particles in which the uncoated part does not substantially exist as coated particles (X). In addition, the surface smoothness (surface roughness) of the particles contained in the raw material powder (A) and the powder (I) can be evaluated by methods such as shape observation by a scanning electron microscope.

[0045] In one embodiment, from the viewpoint of easily obtaining appropriate powder fluidity during the rolling fluidized layer coating process, the average particle density of the raw material powder (A) may be 0.1 to 7.0 g / cm 3 , can also be 0.5~5.5g / cm 3 In addition, the average particle density can be measured by the following method.

[0046] (Method for measuring average particle density)

[0047] 2.0 g of the raw material powder (A) (or powder (I)) is placed in a measuring sample cell of a dry density meter (for example, manufactured by Shimadzu Corporation, product name "AccuPyc II 1340"), and the average particle density is measured by a gas (helium) substitution method.

[0048] In one embodiment, a raw powder (A) may be used that has been surface treated with a surface treatment agent. Since the manufacturing method of this embodiment is coated with the raw powder (A) by rotating fluidized bed coating, it is less susceptible to the surface state of the raw powder (A) than the previous wet coating method. Therefore, a surface-treated raw powder (A) may also be used. Examples of surface treatment agents include silane coupling agents, aluminate coupling agents, and the like. These may be used alone or in combination of two or more. In addition, the presence or absence of surface treatment of the raw powder (A) may be confirmed, for example, by analyzing the raw powder (A) using IR, TG-DTA, mass spectrometry, and the like.

[0049] <Slurry (C) containing coating component (B)>

[0050] The manufacturing method of this embodiment includes the steps of spraying a slurry (C) containing a coating component (B) onto the raw material inorganic metal oxide powder (A) and performing a rotating fluidized layer coating and then sintering. The coating component (B) contained in the slurry (C) may be: a component that can react with the raw material powder (A) to form a coating layer on the surface of particles constituting the raw material powder (A) (hereinafter sometimes referred to as "raw material particles (A)"), or a component that can form a coating layer without reacting with the raw material particles (A). From the viewpoint of facilitating the formation of a uniform and continuous coating layer, a component that can react with the raw material particles (A) to form a coating layer on the surface of the raw material particles (A) is preferred.

[0051] As a coating component (B) that can react with the raw material particles (A), there is no particular limitation as long as it has the effect of the present invention. In one embodiment, as a coating component (B), it is preferred to contain an inorganic metal oxide powder (B1). The inorganic metal oxide powder (B1) contained in the coating component (B) is not particularly limited as long as it can react with the raw material particles (A), but for example, inorganic metal oxide powders such as alumina, silica, and titanium dioxide can be listed. These can be used alone or in combination of two or more.

[0052] In a preferred embodiment, when the coating component (B) contains an inorganic metal oxide powder (B1) (hereinafter sometimes referred to as "powder (B1)"), the median particle size (Db150) of the powder (B1) is preferably 1 to 10000 nm, more preferably 10 to 1000 nm. In addition, in one embodiment, the ratio ((Db150) / (Da50)) of the average particle size (Db150) of the powder (B1) to the median particle size (Da50) of the raw material powder (A) may be 8.0×10 -6 ~1.0×10 -1 , or 5.0×10 -5 ~5.0×10 -2 When ((Db150) / (Da50)) is within the above range, it becomes easy to more efficiently coat the surface of the raw material particle (A) with the coating component (B) containing the powder (B1).

[0053] In one embodiment, when the coating component (B) contains an inorganic metal oxide powder (B1) and the raw material powder (A) contains magnesium oxide powder, the inorganic metal oxide powder (B1) preferably contains at least one inorganic metal oxide powder selected from aluminum oxide (Al2O3) powder and silicon dioxide (SiO2) powder, and more preferably contains aluminum oxide powder. In this case, the coated particles (X) contained in the obtained powder (I) are preferably particles whose surfaces contain core particles containing magnesium oxide and are coated with a coating layer. In addition, the coating layer preferably contains at least one selected from Al2O3, MgO-Al2O3 composite oxide, SiO2 and MgO-SiO2 composite oxide.

[0054] When magnesium oxide powder is used as the raw material powder (A) and coated with inorganic metal oxide powder (B1) such as aluminum oxide, the coated particles (X) preferably contain core-shell particles from the viewpoint that the moisture resistance of the obtained powder (I) is easier to improve. At this time, as the coated particles (X), it is more preferable to be coated particles (X) comprising a core-shell particle whose surface comprises a core particle containing magnesium oxide and is coated with a coating layer containing at least one selected from the above-mentioned Al2O3, MgO-Al2O3 composite oxide, SiO2 and MgO-SiO2 composite oxide. In addition, the coating layer of the above-mentioned core-shell particles preferably contains MgO-Al2O3 composite oxide, and more preferably contains MgAl2O4.

[0055] In one embodiment, the content of the coating component (B) in the slurry (C) may be 0.1 to 80% by mass, or 1 to 50% by mass relative to the total mass of the slurry (C). As long as the content of the coating component (B) is within the above range, it becomes easy to adjust the spraying amount of the coating component (B) relative to the raw material powder (A) to the preferred range described below.

[0056] The dispersion solvent in the slurry (C) preferably contains water or ethanol, and more preferably contains water. The slurry (C) may also contain other components besides the coating component (B) and the dispersion solvent. Examples of other components include a dispersant and a binder.

[0057] In one embodiment, from the viewpoint of being easier to control the value of (Si) / (Sa) to be low, the amount of coating component (B) sprayed relative to raw powder (A) is preferably 1 to 25% by mass relative to the total amount (100% by mass) of raw powder (A) and coating component (B). That is, spraying slurry (C) on raw powder (A) may also be performed in the range of 1 to 25% by mass of coating component (B) relative to the total amount (100% by mass) of raw powder (A) and coating component (B). In other embodiments, from the viewpoint of being easier to obtain core-shell particles, the amount of coating component (B) sprayed relative to the total amount (100% by mass) of raw powder (A) and coating component (B) may also be 1% by mass or more and less than 25% by mass, 1 to 20% by mass, 1% by mass or more and less than 20% by mass, 1 to 18% by mass, or 5 to 20% by mass.

[0058] <Rotary fluidized bed coating>

[0059] The manufacturing method of this embodiment includes the step of spraying the above-mentioned slurry (C) on the raw material powder (A) to perform rotating fluidized bed coating. In addition, rotating fluidized bed coating is also called rotating fluidized coating, rotating fluidized granulation coating, etc., and is a coating method using a coating device equipped with a blade rotor at the bottom of a general fluidized bed device. The present inventors have found that by utilizing rotating fluidized bed coating to spray a slurry (C) containing a coating component (B) on the raw material powder (A) to produce a powder (I) containing coated particles (X), the increase in BET specific surface area caused by coating can be suppressed, and the value of (Si) / (Sa) can be controlled to be less than 5.0. In addition, it has also been found that as long as rotating fluidized bed coating is used, the surface of the raw material particle (A) can be efficiently coated.

[0060] In one embodiment, the tumbling fluidized bed coating may be performed at 20 to 150° C., 30 to 100° C., or 50 to 90° C. In addition, the coating time is not particularly limited as long as the surface of the raw material particles (A) is sufficiently coated. From the perspective of forming a uniform coating layer, it may be 0.01 to 24 hours, 0.05 to 24 hours, or 0.1 to 12 hours.

[0061] Tumbling fluidized bed coating can be performed using a conventionally known tumbling fluidized bed apparatus, for example, a tumbling fluidized bed coating apparatus MP (Multiplex) manufactured by Powrex Corporation can be used.

[0062] <Firing>

[0063] The manufacturing method of the present embodiment includes the step of calcining the raw material powder (A) after the rotating fluidized bed coating. As for the calcination temperature, from the viewpoint of forming a uniform coating layer, it is preferably 500 to 1600°C, more preferably 700 to 1600°C, further preferably 1000 to 1600°C, and particularly preferably 1000 to 1400°C. In one embodiment, it may be more than 1000°C and less than 1600°C, or 1100 to 1500°C. In addition, as for the calcination time, from the viewpoint of forming a uniform coating layer, it is preferably 0.1 to 12 hours, more preferably 0.5 to 10 hours, further preferably 1 to 10 hours, and particularly preferably 1 to 8 hours.

[0064] <Other Processes>

[0065] After the calcination step, the obtained coated powder (A) may become an agglomerate. Therefore, it may be crushed as needed. As a crushing method, it is preferably carried out under conditions where the BET specific surface area (Si) of the powder (I) is difficult to change, for example, a mortar, a bead mill, a ball mill, etc. can be used.

[0066] In one embodiment, after the raw material powder (A) is calcined, the obtained powder (I) may be classified by sieving, airflow classification, etc. By classifying the powder (I), it becomes easy to control (Si) / (Sa) to 5.0 or less.

[0067] [Inorganic metal oxide powder (I)]

[0068] According to the production method of this embodiment, the inorganic metal oxide powder (I) containing the coated particles (X) can be prepared.

[0069] <Coated Particles (X)>

[0070] The coated particles (X) obtained by the manufacturing method of the present embodiment refer to particles whose surface is coated with the coating component (B) at least in part. In a preferred embodiment, the coated particles (X) are preferably core-shell particles having substantially no uncoated portion on their surface. In one embodiment, the coated particles (X) are preferably core-shell particles. In addition, "core-shell particles" refer to coated particles whose surface is mostly coated. Whether the coated particles (X) are core-shell particles can be determined, for example, by using a field emission scanning electron microscope (e.g., manufactured by Carl Zeiss, product name “MERLIN, FE-SEM”) and energy dispersive X-ray spectroscopy (e.g., manufactured by Bruker, product name “QUANTAX System X Flash 6 / 60 SDD, EDS”) to obtain a cross-sectional image of the coated particles (X). When the ratio (rc / ra) of the cross-sectional perimeter ra of the inorganic metal oxide particles (A) (raw material particles (A)) that serve as the core portion to the perimeter rc of the portion of the cross section of the raw material particles (A) that is coated with the coating component (B) is 0.6 or more, it can be determined that most of the core particles are coated with the coating layer (i.e., they are core-shell particles).

[0071] By coating the raw powder (A) with the coating component (B) using the method including the above-mentioned tumbling fluidized bed coating, it is possible to obtain coated particles (X) in which at least a part of the surface of the particles (raw particles (A)) constituting the raw powder (A) is coated with the coating component (B). By adjusting the spraying amount of the above-mentioned coating component (B), adjusting the calcination temperature and the calcination time, etc., it becomes easy to obtain coated particles (X) containing core-shell particles. For example, when magnesium oxide powder is used as the raw powder (A) and the above-mentioned magnesium oxide powder (A) is coated with the coating component (B) containing aluminum oxide powder, the spraying amount of the coating component (B) is set to 1 to 20% by mass relative to the total amount (100% by mass) of the magnesium oxide powder (A) and the coating component (B) in terms of aluminum oxide powder; or by setting the calcination temperature to more than 1000°C and less than 1600°C, etc., it is easy to obtain core-shell particles. Such magnesium oxide powder (I) containing core-shell particles is also easy to have good moisture resistance.

[0072] In one embodiment, from the viewpoint of easily controlling (Si) / (Sa) to 5.0 or less, the proportion of the coated particles (X) in the powder (I) is preferably 80% or more, more preferably 90% or more.

[0073] In one embodiment, the powder (I) may also contain other particles in addition to the coated particles (X). Examples of other particles include uncoated inorganic metal oxide powder (A), particles of inorganic metal oxide or inorganic metal composite oxide derived from the coating component (B), etc. These may contain one kind alone, or two or more kinds.

[0074] In one embodiment, when using a BET specific surface area (Sa) of 0.01 to 10 m 2 When the raw material powder (A) is an inorganic metal oxide powder having a BET specific surface area (Si) of the powder (I), (Si) / (Sa) is in the range of 5.0 or less, preferably 0.015 to 25 m 2 / g, more preferably 0.02 to 20 m 2 / g.

[0075] In one embodiment, when an inorganic metal oxide powder having a median particle size (Da50) of 10 to 150 μm is used as the raw material powder (A), the median particle size (Di50) of the powder (I) is preferably 11 to 300 μm, more preferably 11 to 200 μm, and further preferably 11 to 180 μm.

[0076] In one embodiment, when a powder having an average circularity (ARa) of 0.75 or more is used as the raw material powder (A), the average circularity (ARi) of the powder (I) is preferably 0.75 or more, more preferably 0.80 or more.

[0077] In one embodiment, from the viewpoint of maintaining high thermal conductivity, the thickness of the coating layer calculated as the difference between the median particle size (Di50) of the powder (I) containing the coated particles (X) and the median particle size (Da50) of the raw material powder (A) ((Di50) - (Da50)) may be 40 μm or less, or 35 μm or less. From the viewpoint of easily obtaining a resin composition with a lower viscosity and improving fluidity when filled with a resin, the thickness may be 30 μm or less, or 26 μm or less.

[0078] The powder obtained by coating the particles of the raw material by the conventional coating method such as wet coating, when the raw material powder with low average roundness is used, the average roundness of the obtained powder is also easy to become low. In addition, when the raw material powder with low average roundness is coated, the uncoated part is easy to become more. From the viewpoint of reducing the uncoated part or increasing the average roundness of the coated powder, it is difficult to obtain the desired median particle size (D50) when the coating amount is increased, or the problem of the thermal conductivity being easy to reduce when used as a filler. The powder (I) obtained by the manufacturing method of the present embodiment is easy to obtain a powder (I) with a high average roundness (ARi) even if the raw material powder (A) with low average roundness (ARa) is used. In addition, since the entire particle can be coated with a less coating amount, the thermal conductivity is not easy to reduce.

[0079] <Magnesium oxide powder>

[0080] When the powder (I) obtained by the production method of this embodiment is coated with alumina, silica, etc. on the surface of the raw material powder (A) containing magnesium oxide powder, the obtained magnesium oxide powder has high thermal conductivity and excellent moisture resistance. In one embodiment, the thermal conductivity of the magnesium oxide powder (I) obtained by the production method of this embodiment measured under the following conditions may also be 4.0 to 8.0 W / mK, or 5.0 to 7.0 W / mK.

[0081] (Measurement conditions)

[0082] Mix magnesium oxide powder and spherical aluminum oxide powder (e.g., manufactured by Denka Corporation, product name "DAW-07", product name "ASFP-40", etc.) at a volume ratio of 51:49 to prepare a mixed powder. Fill the mixed powder into a silicone resin (e.g., manufactured by Shin-Etsu Chemical Co., Ltd., product name "SE1885:A", product name "SE1885:B", etc.) so that the ratio of the mixed powder is 77.5% by volume to prepare an evaluation sheet. The evaluation sheet is measured using a thermal resistance measuring machine (e.g., manufactured by Hitachi Technologies and Services Co., Ltd., product name "TRM-046RHHT") to determine the thermal conductivity.

[0083] In addition, the magnesium hydroxide content of the magnesium oxide powder (I) after the test under the following conditions is preferably less than 50% by mass, more preferably 30% by mass or less, and further preferably 10% by mass or less. The magnesium oxide powder (I) obtained by the production method of this embodiment is excellent in moisture resistance, so it is difficult to generate magnesium hydroxide.

[0084] (Measurement conditions of magnesium hydroxide content after test)

[0085] 10 g (M1) of the inorganic metal oxide powder (I) is placed in a highly accelerated life tester (e.g., manufactured by Espec, product name "Highly Accelerated Life Tester EHS-212M", unsaturated mode) at a temperature of 135°C and a humidity of 85 RH% for 168 hours. The mass (M2) of the inorganic metal oxide powder (I) after the standing is measured, and the change in mass before and after the standing is substituted into the following formula (2) to calculate the magnesium hydroxide content.

[0086] {(M2-M1) / 18.0}×(40.3 / M1)×100···(2)

[0087] In formula (2), M1 is the mass (g) of the inorganic metal oxide powder (I) before standing, M2 is the mass (g) of the inorganic metal oxide powder (I) after standing, and 18.0 and 40.3 are the molecular weights of H2O and MgO, respectively.

[0088] [use]

[0089] The powder (I) obtained by the production method of this embodiment has a small increase in the BET specific surface area of ​​the inorganic metal oxide powder obtained in the end relative to the BET specific surface area of ​​the raw material powder, so the fluidity is not easily reduced when filled in the resin. In addition, when the powder (I) is magnesium oxide powder, it has excellent moisture resistance and good thermal conductivity. Such a powder (I) can be preferably used as a filler for resin.

[0090] [Resin composition]

[0091] The resin composition of the present embodiment contains the powder (I) prepared by the above-mentioned production method and at least one resin selected from thermoplastic resins and thermosetting resins.

[0092] The content of the powder (I) in the resin composition is not particularly limited and can be appropriately adjusted according to the purpose. For example, when used for sealing materials, it can be blended in the range of 1 to 99 mass %, more preferably 10 to 90 mass %, relative to the total mass of the resin composition.

[0093] <Resin>

[0094] The resin composition of the present embodiment contains at least one resin selected from thermoplastic resins and thermosetting resins. More specifically, for example, polyethylene resins; polypropylene resins; epoxy resins; silicone resins; phenolic resins; melamine resins; urea resins; unsaturated polyester resins; fluororesins; polyamide resins such as polyimide resins, polyamide-imide resins, and polyetherimide resins; polyester resins such as polybutylene terephthalate resins and polyethylene terephthalate resins; polyphenylene sulfide resins; fully aromatic polyester resins; polysulfone resins; liquid crystal polymer resins; polyethersulfone resins; polycarbonate resins; maleimide modified resins; ABS resins; AAS (acrylonitrile-acrylic rubber-styrene) resins; AES (acrylonitrile-ethylene-propylene-diene rubber-styrene) resins; hydrocarbon elastomer resins; polyphenylene ether resins; aromatic polyene resins, etc. These can be used alone or in combination of two or more.

[0095] The resin composition of the present embodiment may contain a curing agent, a curing accelerator, a release agent, a coupling agent, a coloring agent, a flame retardant, an ion scavenger, and the like within a range not inhibiting the effects of the present invention.

[0096] <Method for producing resin composition>

[0097] The manufacturing method of the resin combination is not particularly limited, and can be manufactured by stirring, dissolving, mixing, and dispersing the specified amount of each material. The devices for mixing, stirring, and dispersing these mixtures are not particularly limited, but can use: a crushing machine, a three-roller mill, a ball mill, a planetary mixer, etc. equipped with a stirring and heating device. In addition, these devices can also be used in appropriate combination.

[0098] As described above, the resin composition containing the coated powder (A) has excellent fluidity and good handling properties.

[0099] More preferred embodiments of this embodiment are as follows.

[0100] <1> A method for producing a magnesium oxide powder (I) containing coated particles (X), wherein:

[0101] The production method comprises the steps of spraying a slurry containing at least one coating component (B) selected from alumina powder and silica powder onto a raw material magnesium oxide powder (A), performing a tumbling fluidized bed coating, and then calcining to obtain magnesium oxide powder containing coated particles (X); and

[0102] The ratio of the coating component (B) sprayed onto the magnesium oxide powder (A) is 1% by mass or more and less than 25% by mass relative to the total amount (100% by mass) of the magnesium oxide powder (A) and the coating component (B),

[0103] The ratio of the BET specific surface area (Si) of the magnesium oxide powder (I) to the BET specific surface area (Sa) of the magnesium oxide powder (A) ((Si) / (Sa)) is 5.0 or less.

[0104] <2> like <1> The described production method, wherein the coating component (B) contains alumina powder, and the ratio of the alumina powder sprayed on the magnesium oxide powder (A) is 1 to 20 mass % relative to the total amount (100 mass %) of the magnesium oxide powder (A) and the coating component (B).

[0105] <3> like <1> or <2> In the described production method, the sintering temperature is higher than 1000°C and lower than 1600°C.

[0106] <4> like <1> to <3> A manufacturing method as described in any one of the items, wherein the coated particles (X) contain core-shell particles whose surfaces contain core particles containing magnesium oxide and are coated with a coating layer containing at least one selected from Al2O3, MgO-Al2O3 composite oxide, SiO2 and MgO-SiO2 composite oxide.

[0107] <5> like <1> to <4> The production method according to any one of claims , wherein the slurry is sprayed onto the magnesium oxide powder (A) so that the thickness of the coating layer of the coated particles (X) becomes 30 μm or less.

[0108] Example

[0109] The present invention will be described in detail below with reference to Examples, but the present invention is not limited to the following description.

[0110] [Example 1]

[0111] Magnesium oxide powder (manufactured by Denka Corporation, trade name "DMG-50", median particle size (Da50): 50 μm, BET specific surface area (Sa): 0.2 m 2 / g, average roundness (ARa): 0.93) as a raw material powder (A), a slurry (C) containing alumina powder (coating component (B), manufactured by Cabot Specialty Chemicals Inc., product name "CAB-O-SPERSE PG008", median particle size (Db150): 100nm) is sprayed on the magnesium oxide powder (A) and a rotating fluidized layer coating is performed. The slurry (C) is sprayed on the magnesium oxide powder (A) in an amount such that the ratio of the coating component (B) to the total amount (100% by mass) of the magnesium oxide powder (A) and the coating component (B) is 7% by mass (93% by mass of magnesium oxide powder (A), 7% by mass of the coating component (B) (converted to alumina powder)). Thereafter, the magnesium oxide powder (I) is obtained by calcining at 1300°C for 1 hour (powder (I)). The (Si), median particle size (Di50), average roundness, and presence or absence of coated particles (X) of the obtained powder (I) were measured under the following conditions. In addition, the physical properties of the raw powder (A) are also values ​​measured under the same conditions as the powder (I). In addition, the thickness of the coating layer was calculated from the difference between the median particle size (Da50) of the raw powder (A) and the median particle size (Di50) of the powder (I). The results of these measurements showed that the powder (I) of Example 1 contained coated particles (X), and further (Si) / (Sa) was 0.70.

[0112] (Measurement method of BET specific surface area (Sa) and (Si))

[0113] The specific surface area was measured by filling 5 g of the raw material powder (A) (or powder (I)) in the measuring tank of a fully automatic specific surface area measuring device (BET one-point method) (Macsorb HM model-1201 fully automatic specific surface area measuring device manufactured by Mountech). The degassing conditions before the measurement were set at 200° C. and 10 minutes. In addition, helium and nitrogen (mixed concentration: 30.5%) were used as carrier gas and adsorption gas, respectively.

[0114] (Method for measuring median particle size (D50))

[0115] The median particle size (D50) of the powder was determined by volume-based particle size distribution measurement using a laser diffraction particle size distribution measuring apparatus (manufactured by Beckman Coulter, Inc., product name "LS13 320"). 3 0.1 g of the raw material powder (A) (or powder (I)) and 0.1 g of pure water were mixed with an ultrasonic homogenizer (manufactured by MicrotecNition (Co., Ltd.), product name "Smurt NR-50M (Titanium Alloy Chip)"). (NS-50M-MT3))")), and the dispersion treatment was carried out for 60 seconds at an output of 25W. The dispersion liquid of the above-mentioned raw material powder (A) (or powder (I)) that had been dispersed was added drop by drop with a dropper to the above-mentioned laser diffraction particle size distribution measuring device, and the measurement was carried out 30 seconds after the addition of the specified amount. In addition, the refractive index of water was set to 1.33, and the refractive index of MgO powder was set to 1.74. The median particle size (D50) was calculated from the particle size corresponding to 50% of the cumulative value in the volume-based cumulative particle size distribution of the measured particle size.

[0116] (Average roundness)

[0117] After fixing the raw material powder (A) (or powder (I)) with a carbon tape, osmium coating is performed. Thereafter, the particles are photographed at a magnification of 200 to 50,000 times using a scanning electron microscope (manufactured by JEOL Ltd., product name "JSM-7001F SHL"), and the projected area (A) of the particles is calculated using an image analyzer (for example: manufactured by Nippon Roper Ltd., product name "Image-Pro Premier Ver. 9.3"). p ) and the projected circumference (L), the circularity is calculated by the following formula (1). The circularity is calculated for any 200 particles and the average value is taken as the average circularity.

[0118] Roundness = 4πA p / L 2 ···(1)

[0119] <Presence or absence of coated particles (X) and core-shell particles>

[0120] The powder (I) obtained in Example 1 was observed using a scanning electron microscope (manufactured by JEOL Ltd., device name “JSM-7001F”) to confirm the presence or absence of coated particles (X). In addition, for the powder (I), the presence or absence of coated particles (X) was calculated using a field emission scanning electron microscope (manufactured by Carl Zeiss, product name “MERLIN, FE-SEM”) and an energy dispersive X-ray spectrometer (manufactured by Bruker, product name “QUANTAX System The presence or absence of core-shell particles was confirmed by measuring the ratio (rc / ra) of the cross-sectional perimeter ra of the coated particles in the cross-sectional image obtained by XFlash6 / 60SDD, EDS”) to the perimeter rc of the portion coated with the coating component (B) in the cross-sectional image of the coated particles. At this time, the measurement was carried out at an image acquisition magnification of 1000 times, a voltage of 10 kV, a current of 500 nA, and a measurement time of 30 seconds, and element mapping was performed for aluminum and magnesium. In addition, image analysis was carried out using ImageJ, and for a particle image, the perimeter of the mapping portion of the magnesium component that would become the core was set to ra, and the perimeter of the portion of the surrounding portion of the magnesium component that was in contact with the aluminum component that would become the shell (when the portion only 1 pixel outside the surrounding portion of the magnesium was the mapping portion of the aluminum component, it was judged to be “in contact”) was set to rc, and rc / ra was calculated, and rc / ra was judged to be 0.6 or more as core-shell particles. The results are shown in Table 1.

[0121] <Liquidity Evaluation>

[0122] With respect to the powder (I) obtained in Example 1, a resin composition was prepared under the following conditions.

[0123] 60% by volume of a bisphenol A type liquid epoxy resin (epoxy equivalent: 184 to 194, manufactured by Mitsubishi Chemical Corporation, product name "JER828") and 40% by volume of powder (I) were mixed and kneaded using a planetary mixer (manufactured by Thinky Corporation, product name "Thinky Mixer (registered trademark) AR-250", rotation speed 2000 rpm) to prepare a resin composition.

[0124] Next, the viscosity of the obtained resin composition at 25° C. was measured under the following conditions. In addition, evaluation was performed according to the following evaluation criteria, and an evaluation of “OK” or higher was considered acceptable (good fluidity). The results are shown in Table 1.

[0125] The viscosity at 25° C. of the obtained resin composition was measured under the following conditions using a rotational rheometer (manufactured by Anton Paar, product name “MCR-302”).

[0126] Tablet shape: round tablet

[0127] Sample thickness: 1mm

[0128] Temperature: 25±1℃

[0129] Shear speed: 1.0 / s

[0130] (Evaluation Criteria)

[0131] Good: The viscosity of the resin composition is 500 Pa·s / 25°C or less.

[0132] Good: The viscosity of the resin composition is more than 500 Pa·s / 25°C and 1000 Pa·s / 25°C or less.

[0133] The viscosity of the resin composition may be more than 1000 Pa·s / 25°C and less than 2000 Pa·s / 25°C.

[0134] Not allowed: The viscosity of the resin composition exceeds 2000 Pa·s / 25°C.

[0135] <Thermal conductivity evaluation>

[0136] The thermal conductivity when the powder (I) of Example 1 is used as a filler is evaluated. First, the powder (I) and spherical alumina powder (a mixture of product names "DAW-07" and "ASFP-40" manufactured by Denka Corporation, (DAW-07) / (ASFP-40)=70 / 30 (volume ratio)) are mixed in a volume ratio of 51:49 to prepare a mixed powder. The mixed powder is filled in a silicone resin (a mixture of product names "SE1885:A" and "SE1885:B" manufactured by Shin-Etsu Chemical Co., Ltd., (SE1885:A) / (SE1885:B)=50 / 50 (volume ratio)) in such a manner that the ratio of the mixed powder becomes 77.5% by volume, and mixed using a mixer with stirring blades to obtain a resin composition. The resin composition is molded using a sheet coater to obtain a sheet for evaluation having a thickness of 3 mm. The evaluation sheet was measured using a thermal resistance measuring machine (manufactured by Hitachi Technologies and Services Co., Ltd., product name "TRM-046RHHT") to determine the thermal conductivity.

[0137] [Examples 2 to 9]

[0138] Powder (I) was prepared in the same manner as in Example 1 except that the raw material powder (A) and coating conditions were set as shown in Table 1. For the powder (I) and raw material powder (A) of each example, (Sa), (Si), median particle size (D50), average roundness, presence or absence of coated particles (X), thickness of the coating layer, fluidity evaluation and thermal conductivity evaluation were performed under the same conditions as in Example 1. The results are shown in Table 1. In addition, the silica powder of Examples 8 to 9 was manufactured by Cabot Specialty Chemicals Inc., product name "CAB-O-SPERSE 2017A" (median particle size (Db1): 100 nm).

[0139] [Comparative Example 1]

[0140] Magnesium oxide powder (manufactured by Denka Corporation, trade name "DMG-50", median particle size (Da50): 50 μm, BET specific surface area (Si): 0.2 m 2 / g, average roundness (ARa): 0.93) as raw material powder (A), the above magnesium oxide powder (A) was immersed in alumina slurry (coating component (B), Cabot Specialty Chemicals Inc., product name "PG008", median particle size (Db150): 100nm) for 1 hour for wet coating, and then calcined at 1300°C for 2 hours. The various physical properties of the obtained powder were evaluated by the same method as in Example 1. The results are shown in Table 1.

[0141] Table 1

[0142]

[0143] As shown in Table 1, the (Si) / (Sa) of the powders (I) of Examples 1 to 9 obtained by the manufacturing method of the present embodiment is less than 5.0. The viscosity of the resin composition filled with the powders (I) of these Examples at 25°C is less than 2000 Pa·s, and the fluidity is also good. On the other hand, the viscosity of the resin composition filled with the powder of Comparative Example 1 coated by wet coating exceeds 2000 Pa·s at 25°C, and the fluidity is poor. From the above results, it is confirmed that the BET specific surface area of ​​the inorganic metal oxide powder (I) finally obtained by the manufacturing method of the present embodiment is small relative to the increase in the BET specific surface area of ​​the raw material powder, and the fluidity is not easily reduced when filled in the resin.

[0144] Industrial availability

[0145] The production method of this embodiment can provide an inorganic metal oxide powder containing coated particles whose fluidity is not easily reduced when filled in a resin. A resin composition containing such a powder can be used as a ceramic filler for semiconductor sealing materials and the like.

Claims

1. A method for producing an inorganic metal oxide powder I, which is a method for producing an inorganic metal oxide powder I containing coated particles X, The production method comprises the steps of spraying a slurry C containing a coating component B onto an inorganic metal oxide powder A as a raw material, performing a tumbling fluidized bed coating, and then calcining to obtain an inorganic metal oxide powder I containing coated particles X. in, The ratio Si / Sa of the BET specific surface area Si of the inorganic metal oxide powder I to the BET specific surface area Sa of the inorganic metal oxide powder A is 5.0 or less.

2. The method for producing the inorganic metal oxide powder I according to claim 1, wherein: The firing temperature is 500-1600°C.

3. The method for producing the inorganic metal oxide powder I according to claim 1 or 2, wherein: The firing time is 0.1 to 12 hours.

4. The method for producing the inorganic metal oxide powder I according to claim 1 or 2, wherein: The inorganic metal oxide powder A is sprayed with the slurry C under the following conditions: The above conditions are such that the ratio of the coating component B is in the range of 1 to 25% by mass relative to the total amount of the inorganic metal oxide powder A and the coating component B (100% by mass).

5. The method for producing the inorganic metal oxide powder I according to claim 1 or 2, wherein The median particle size Da50 of the inorganic metal oxide powder A is 10 to 150 μm. The median particle size Di50 of the inorganic metal oxide powder I is 11 to 300 μm.

6. The method for producing the inorganic metal oxide powder I according to claim 1 or 2, wherein: The Si / Sa is greater than or equal to 0.

5.

7. The method for producing the inorganic metal oxide powder I according to claim 1 or 2, wherein: The coating component B contains an inorganic metal oxide powder B1.

8. The method for producing the inorganic metal oxide powder I according to claim 1 or 2, wherein: The coated particles X contain core-shell particles.

9. The method for producing the inorganic metal oxide powder I according to claim 1 or 2, wherein: The inorganic metal oxide powder A includes an inorganic metal oxide powder or an inorganic metal composite oxide powder containing at least one element selected from the group consisting of titanium, aluminum, magnesium, silicon, and calcium.

10. The method for producing the inorganic metal oxide powder I according to claim 1 or 2, wherein: The inorganic metal oxide powder A contains magnesium oxide powder, The coating component B contains at least one inorganic metal oxide powder B1 selected from alumina powder and silica powder. The coated particles X include particles in which the surface of a core particle containing magnesium oxide is coated with a coating layer.

11. The method for producing the inorganic metal oxide powder I according to claim 10, wherein: The coating layer contains at least one selected from Al2O3, MgO-Al2O3 composite oxide, SiO2, and MgO-SiO2 composite oxide.

Citation Information

Patent Citations

  • Method for manufacturing coated magnesium oxide powder

    JP2003034523A

  • Coated magnesium oxide powder, its production method, and resin composition comprising the same

    JP2008074683A